Lived scarcity, social attitudes and political behaviour in Kenya : evidence from Afrobarometer Round 5 - Isbell, Thomas Alexander (Department of Political Studies, 2016)
In this thesis I examine the causal linkages between natural resource scarcity and violence. In contrast to previous research, I posit that scarcity is an inherently personal experience, and thus argue that the consequences of scarcity too, should be empirically tested at the individual level. The available literature has heavily relied on macro- level aggregate data, often producing inconclusive findings on the exact causality between scarcity and violence. Based on the theoretical work by Thomas Homer- Dixon, I apply micro- level household survey data in a multi- stage structural equation model to test the effect of people's social and political perceptions and attitudes on the linkage between scarcity and violence. I find both direct and indirect significant linkages between respondents' experienced scarcity ('lived scarcity') and their propensity to use violence. I find that the indirect effect on violence is explained by decreases in policy satisfaction, political trust and state legitimacy, and increases of more positive attitudes towards violence. From this, I suggest that experienced scarcity is 'politicized' by respondents as a policy failure, rather than being perceived as exogenous to the political system. My analysis supports the relevance of conditional meso- level factors, and finds strong differences between moderator groups regarding their propensity to use violence. While I find that the highest levels of use of violence in Kenya are driven by political competition, rather than ethnic competition, my path models clearly demonstrate that experienced food scarcity is a significant root cause of this violence through its effect on how people 'politicize' the experience of scarcity. Overall, the models suggest that the effects of scarcity are more complex than previously acknowledged. The risk of violence should thus not be estimated only through direct effects between scarcity and violence, but the risk should be understood in terms of both immediate, direct effects, and mid- and long- term, indirect effects such as decreased levels of political trust, lower perceptions of state legitimacy and more accepting attitudes towards violence.